(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
New structural and biostratigraphic data, mainly based on conodonts, permit the recognition of three different sub-units within the Hercynian Arburese Tectonic Unit of SW Sardinia, which are here described. Some stages and conodont biozones of Silurian-Early Devonian age are reported for the first time in Sardinia.